Novel Benzo-1,3,6-Thiadiazepines; Synthesis, Antimicrobial Activity and Isomerization into Benzo-1,3,5-Triazepines - P. Deohate, Pradip; P. Deohate, Jyoti; Berad, B.N. (Asian Journal of Chemistry, 2016)
Benzo-(4,5-d)-2-phenylimino-7-aryl/alkylimino-1,3,6-thiadiazepines (IVa-g) have been obtained by the basification of benzo-(4,5-d)-2-phenylimino-7-aryl/alkylimino-1,3,6-thiadiazepine hydrochlorides (IIIa-g). The latter were synthesized by the interaction of N-phenyl isocyano dichloride and 1-aryl/alkyl-3-(2'-amino)phenyl thiocarbamides (IIa-g), which were prepared initially by the condensation of aryl/alkyl isothiocyanates (Ia-g) and o-phenylenediamine. Compounds (IVa-g) on acylation with acetic anhydride and glacial acetic acid in 1 : 2 ratio afforded 3,6-diacetyl derivatives (Va-g) and on boiling with aqueous ethanolic sodium hydroxide solution isomerized into corresponding benzo-1,3,5-triazepines (VIa-g). The title compounds were assayed for their antimicrobial activity against gram-positive as well as gram-negative microorganisms such as E. coli, S. aureus, S. typhi, B. subtilis, A. aerogenes and A. niger.